Bioproducts for Health II - Pintado, Manuela; Coscueta, Ezequiel; Brassesco, María Emilia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In order to build a promising future, health and sustainability must be interelated. Marine, forestry, agriculture, and food systems are important sources of bioproducts used in health applications. To explore the potential of such sources for the development of natural products capable of biological activities, it is necessary to develop new technologically sustainable strategies. Despite the range of natural compounds already available, there is a need to identify bioactive molecules (e.g., polysaccharides, proteins and peptides, polyunsaturated fatty acids, and polyphenols) from different natural sources with positive health properties, including antihypertensive, antidiabetic, anti-obesity, antimicrobial, anti-atherosclerotic, antioxidant, antithrombotic, immune-modulatory, relaxing, and satiety-inducing effects. The Second Edition of this Special Issue aimed to identify and gather works on the latest varied sources of bioproducts, the biological and functional activities of these bioactive compounds, their mechanisms of action, and the methods used for extraction and purification, without losing our focus on alignment with the concept of green technology.